Fostering Students' Attitudes Towards STEM Using STEM Project-Based Learning in Learning Optical Instruments - Muntaz, Adinda Zaskia Yasmin; Winarno, Nanang; Ashidiq, Rizki Maulana; Sujito, Sujito (JURNAL PENDIDIKAN SAINS (JPS), 2024)
Education is a key driver in cultivating a skilled generation, providing innovative STEM learning to enhance future prospects. This research analysed the effect of STEM project-based Learning in optical instrument topics on students' attitudes and perception towards STEM. Conducted through a quasi-experimental method, the research drew its sample from 8th-grade students in a junior high school in Bandung, Indonesia, evenly split between control (n=30) and experimental (n=30) classes. The control class is taught by project-based learning, while STEM PJBL taught to the experimental class. The result of this study was an N-Gain of students' attitudes towards STEM in experimental class showed a 0.11, which is still categorized as low enhancement. The T-test result (asymp. sig. (2-tailed) = 0.54) also shows no significant difference between the control and experimental classes. Furthermore, engineering and technology are favored STEM subscale, seen as fostering creativity subscale, followed by science, which students' enjoy most of science with no counting lesson, However, most students hold a negative view of mathematics subscale due to the complexity of formulas provided in the lesson. Based on this research, STEM-PJBL should be applied in creative, innovative, and consistent ways within the science class to get a higher shift in students' attitudes.